Psychosocial factors associated with an MRI diagnosis of chronic non-specific low back pain in Saudi Arabia - Alhowimel, Ahmed (2019)
Introduction In patients with chronic low back pain, psychosocial factors have a considerable influence on pain perceptions. These factors also affect treatment and rehabilitation responses, as well as increasing the probability of disability associated to back pain. It is postulated in various studies that in low back pain (LBP) patients, there could be a relationship between psychosocial factors, including catastrophising and fear avoidance, and treatment responses. However, at this time, the research exploring this relationship of psychosocial factors as predictors of pain and disability outcomes in chronic low back pain (CLBP) is insufficient.